2013
DOI: 10.1111/liv.12179
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline vs terlipressin in the treatment of type 2 hepatorenal syndrome: a randomized pilot study

Abstract: The results of this randomized study suggest that terlipressin and noradrenaline are safe and effective in the treatment of type 2 HRS and baseline serum creatinine, urine output and urinary sodium are predictive of response. Noradrenaline is less expensive than terlipressin in the treatment of type 2 HRS (ClinicalTrials.gov, Number NCT01637454).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 32 publications
2
89
0
Order By: Relevance
“…13,27 The results of the current study confirm findings from previous investigations showing that treatment with terlipressin and albumin is effective in improving kidney function and inducing reversal of type 2 HRS. 6,8,16,18,[28][29][30] In fact, 61% of patients treated in our study showed reversal of type 2 HRS, with marked improvement of kidney function that was associated with improvement in circulatory function. A remarkable finding, however, was the high relapse rate observed in responders.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…13,27 The results of the current study confirm findings from previous investigations showing that treatment with terlipressin and albumin is effective in improving kidney function and inducing reversal of type 2 HRS. 6,8,16,18,[28][29][30] In fact, 61% of patients treated in our study showed reversal of type 2 HRS, with marked improvement of kidney function that was associated with improvement in circulatory function. A remarkable finding, however, was the high relapse rate observed in responders.…”
Section: Discussionmentioning
confidence: 51%
“…Relapse of HRS has also been reported in a few other studies, and it appears to be more common in type 2 HRS than in type 1 HRS. 17,18 Although the pathogenic mechanism underlying this high relapse rate was not evaluated in this investigation, it could be related to a deterioration of circulatory function after suppression of vasoconstrictor treatment, with rebound activation of vasoconstrictor systems and return to kidney hypoperfusion.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One small pilot study (N=12) looked at the effect of norepinephrine and found norepinephrine effective. 2 One study found that norepinephrine had similar outcomes compared to terlipressin 3 . However, the use of norepinephrine on general medical wards is usually not possible, and therefore was not an option for our patient.…”
Section: Literature Reviewmentioning
confidence: 99%